2006
DOI: 10.1007/s10584-005-9024-z
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium

Abstract: In recent years, the phenomenon of global warming and its implications for the future of the human race have been intensively studied. In contrast, few quantitative studies have been attempted on the notable effects of past climatic changes upon human societies. This study explored the relationship between climatic change and war in China by comparing high-resolution paleoclimatic reconstructions with known war incidences in China in the last millennium. War frequencies showed a cyclic pattern that closely fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 23 publications
5
127
3
Order By: Relevance
“…More recent breakthroughs came from research adopting quantitative approaches to all known cases of social crisis. These studies show that, in recent history, climate change was responsible for the outbreak of war, dynastic transition, and population decline in China, Europe, and around the world because of climate-induced shrinkage of agricultural production (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the underlying causal linkages from climate change to agricultural production and various human catastrophes in history have not been addressed scientifically.…”
mentioning
confidence: 99%
“…More recent breakthroughs came from research adopting quantitative approaches to all known cases of social crisis. These studies show that, in recent history, climate change was responsible for the outbreak of war, dynastic transition, and population decline in China, Europe, and around the world because of climate-induced shrinkage of agricultural production (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the underlying causal linkages from climate change to agricultural production and various human catastrophes in history have not been addressed scientifically.…”
mentioning
confidence: 99%
“…Jamestown Colony, settled nearby two decades later, almost collapsed during a similar drought. Zhang et al (2006) examine Chinese records from 1000-1911 and find cold periods of 10-100 years were associated with higher frequencies of war, rebellion, population decline and all five dynastic transitions. Zhang et al argue that in temperate China, cold temperatures reduced yields, triggering civil unrest and political instability.…”
Section: Africa and The Middle Eastmentioning
confidence: 99%
“…Moreover, previous work has shown that low temperatures are also correlated with belowaverage population growth in China over the past millennia (Lee et al 2008). Decreasing food yields induced by a deteriorating climate was unable to support surplus population growth during the warm periods (Lee et al 2008;Zhang et al 2006). Moreover, sustainable economic development became more susceptible to disturbances from social unrest and war , particularly considering that regional climate changes would produce different effects on the Sino society and nomadic society (Fang and Liu 1992).…”
Section: Potential Mechanism For Climatic Effectsmentioning
confidence: 99%
“…Using long-term historical records to reconstruct a socioeconomic proxy and to quantitatively study the relationship between climate change and historical rhythms has been an advantage in China for climate sociology research (Fang et al 2013;Ye et al 2012;Su et al 2014;Zhang et al 2006;Lee et al 2008). Previous studies paid more attention to the climatic effects on historical cyclical rhythms based on population (Lee et al 2008), the frequency of revolts and wars (Zhang et al 2010c;Zhang et al 2006) and dynastic collapse events .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation